2015
DOI: 10.1002/ddr.21262
|View full text |Cite
|
Sign up to set email alerts
|

Co‐administration of N‐Acetylcysteine and Acetaminophen Efficiently Blocks Acetaminophen Toxicity

Abstract: Preclinical Research Although acetaminophen (APAP) is an effective analgesic and anti-pyretic, APAP overdose is the most frequent cause of serious, often lethal, drug-induced hepatotoxicity. Administration of N-acetyl cysteine (NAC) within 8 hours of APAP overdose effectively mitigates APAP-induced hepatotoxicity. Thus, preventing APAP toxicity before it occurs by formulating APAP with NAC is logical and, as we show here in a mouse model, is effective in preventing APAP toxicity. Thus, toxic oral APAP doses su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
4
15
0
Order By: Relevance
“…Till date, only few studies have reported this fact. However, NAC has been demonstrated as a potential antidote for the treatment of thinner and acetaminophen-intoxicated patients or as nephroprotective agent to attenuate chemical or biochemical and electrolytes imbalance [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Till date, only few studies have reported this fact. However, NAC has been demonstrated as a potential antidote for the treatment of thinner and acetaminophen-intoxicated patients or as nephroprotective agent to attenuate chemical or biochemical and electrolytes imbalance [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…On the ninth day, 24 h post last toxic APAP dose, [17,18,19] all rats were euthanized by cervical dislocation, and blood samples were withdrawn by cardiac puncture, collected in sterile plain centrifugation tubes and left at room temperature for 15 min to clot completely. After that, serum was obtained by centrifugation at 6000 rpm for 10 min at room temperature and kept at −20 °C until further testing.…”
Section: Methodsmentioning
confidence: 99%
“…N -acetylcysteine is a drug that replenishes GSH stores in vivo ( 98 ) . Co-administration of APAP and N -acetylcysteine could prevent acute APAP toxicity, as has been shown in a preclinical study ( 99 ) .…”
Section: Paracetamol Detoxification Induces An Irreversible Loss Of Cmentioning
confidence: 58%